An integrated decision support system for building asset management based on BIM and Work Breakdown Structure. (February 2021) - Al-Kasasbeh, Maha; Abudayyeh, Osama; Liu, Hexu
Abstract: The asset management phase of a building constitutes approximately 60% of its total lifecycle costs. However, significant unnecessary expenses occur in current asset management practices because of the separation of the design and construction phases from operation and maintenance and the lack of an effective building asset management system covering all types of buildings with numerous components. Asset management decision-making is inherently a process that requires the assimilation of a multitude of data, processes, and software systems. Therefore, this paper proposes an integrated decision support system for building asset management that addresses the systematization and coordination of lifecycle data. In this approach, a lifecycle work breakdown structure (WBS) for the asset management system is developed to provide a unified hierarchy to categorize and organize building assets. It is then used to develop the WBS-based integrated building lifecycle asset management model through a relational database management system (DBMS). Since building information modelling (BIM) is a rich information-based platform with large volumes of asset data needed, it is integrated with the WBS-based DBMS to achieve an effective integrated building asset management. A case study of an educational building is presented and discussed in the paper to demonstrate how the proposed automated solution is used for asset management. The research contributes to the body of knowledge by formalizing a WBS-based unified asset inventory hierarchy and mapping BIM data to the proposed hierarchy for effective asset management. Highlights: A life-cycle work breakdown structure (WBS) for asset management system is developed. A relational database management system (DBMS) is developed based on the proposed WBS. BIM and DBMS are integrated for asset management decision support system. An educational building case study is presented to demonstrate the developed system. The proposed system addresses the systematization and coordination of life-cycle facility data.